Criteria Field and Diagnostic Tools for Determining the Emotional Well-Being of Preschool Children in the Family and Educational Organization - E.I. Izotova; I.A. Burlakova; O.V. Nikiforova; N.S. Korshunova (Moscow State University of Psychology and Education, 2024)
The article is devoted to the important problem of identification of the emotional well-being of preschool children in the family and educational organization. Basing on the analysis of existing approaches to this problem in Russian psychological and pedagogical science, the authors have identified the criteria field of the concept of "emotional well-being", which is a complex level structure of interrelated criteria and indicators: emotional background (manifestation of emotions), the ability to control emotions (emotional stability) and emotional perception of situations (emotional attitude to situations and events). Such manifestations in the behavior and activities of a child, depending on the conditions of his life in a family or educational organization, are negative or positive. The complexity of the concept of "emotional well-being" and the criteria field of its identification in childhood requires an integrated approach to the development of diagnostic tools. The authors announced a developed set of diagnostic tools, which includes methods that allow to record external indicators of the emotional state of a child, to identify the child's internal emotional attitude to current or predicted events, as well as to obtain an external indirect assessment of the child's subjective state and the child's subjective attitude to situations in the family and educational organization. It is noted that the announced methods can be used in the practice of preschool education in order to support psychological and pedagogical development of preschool children including various target groups, as well as in the targeted psychological assistance of families with preschool children.